Training assessment, key in the management of the teaching - learning process - Montes Yacsahuache, Aurora Elizabeth; Mancilla Curi, Benita Sonia; Rivera Rojas, Claudia Noemi; Bernardo Zarate, Carlos Enrique (Revista Iberoamericana de educación, 2021)
The present research "The formative evaluation, key in the management of the teaching - learning process in students of a state university in the district of Chosica - Lima, 2020" aimed to determine the effects of the formative evaluation in the management of teaching processes and learning carried out by students in pre-professional practice. The method was of a quantitative approach, of an applied type and a quasi-experimental design. The sample consisted of 240 students. Being 120 students the control group and 120 of the experimental group. Observation was used as a technique and the observation guide as an instrument. It was concluded that the application of the program "With formative evaluation I manage significant learning" improves the levels of management of teaching - learning processes.